(untitled) (Research, Society and Development, 2021)
Non-woven polypropylene (PP) sorbents are materials that can be used in oil recovery following spills, which are interesting alternatives to remediate contaminated areas. This work aimed to characterize a non-woven sorbent made of PP. The physicochemical characteristics of the material, sorption capacity, kinetics, and adsorption isotherms were evaluated. The physicochemical study included the determination of thickness, density, thermal and chemical properties of the sorbent, and fiber morphology. Sorption tests were performed according to the standard method ASTM 726-12. The kinetic models of pseudo-first and pseudo-second order were tested. The fit of the experimental data to the adsorption isotherms of Langmuir, Freundlich, and Temkin was also carried out. The sorbates used in the tests were diesel, petroleum, and lubricant oil. The sorption capacity of the PP nonwoven blanket relative to diesel, petroleum, and lubricant oil in long-term tests was 5.3, 12.3, and 18.7 g∙g-¹, with increasing values when sorbates were more viscous. The results of the short and long-term tests did not show a statistical difference in the sorption capacity of the blanket. The kinetic study showed that the sorption of the three sorbates followed pseudo-second-order kinetics. The diesel oil presented a better fit to the Langmuir isotherm (R² = 0.998), whereas the petroleum presented an excellent fit to all three isotherms (R² = 0.996-0.999). Regarding sorbent reusability, the sorption capacity stabilized after the second cycle, and the samples whose sorbate removal was carried out by centrifugation have presented and maintained the highest sorption capacities.